The Relationship of Attitude, Perceived Behavioral Control, Subjective Norm on Halal Food Purchasing Behavior on Indonesian Muslim Millennials - Siti Salmah; Anwar Adem Shikur (Ekonomi Islam Indonesia, 2023)
Currently, halal food is one of the interesting topics to research, especially in Indonesia, because halal food has great potential and contribution in the halal sector. This study aims to examine the purchasing behavior of halal food among generation z Muslims in Indonesia. Respondents were randomly selected from generation z Muslims who consume halal food through questionnaires, resulting in 179 respondents. This study uses Structural Equation Modeling (SEM), showing a positive and significant relationship between attitude and purchase intention, perceived behavioral control and purchase intention, perceived behavioral control and satisfaction, purchase intention and satisfaction. This is in accordance with the Theory of Planned Behavioral applied in this study. Meanwhile, subjective norms and purchase intention showed a positive but insignificant relationship with the model tested. This study contributes to understanding halal food purchasing behavior, especially for generation z Muslims and the level of consumer satisfaction with these products and as an evaluation material for halal food entrepreneurs. Keywords: ; Z;